Evaluation of the effect of one-stage transanal endorectal pull-through (TERPT) technique on defecation in patients with Hirschsprung’s Disease over the last 10 years in Tehran Pediatrics Medical Center - Ghavami Adel, Maryam; Ashjaei, Bahar; Sinafar, Sima; Maghbouli, Leili; Parizad, Jaleh; Gharib, Behdad; Khosravi, Rahman (Iranian Journal of Pediatric Surgery, 2018)
Introduction: One-stage Transanal Endorectal Pull-Through (TERPT) is one of the methods used for the treatment of Hirschsprung’s disease. The purpose of our study was to evaluate complications of surgery specially does related to defecation in patients undergoing pull-through surgery in Tehran Pediatrics Medical Center during the past 10 years. Materials and Methods: This descriptive study was performed on patients undergoing one-stage TERPT operation in Tehran Pediatrics Medical Center over the past 10 years. Exclusion Criteria included: the parent’s lack of consent to participate in the study, age below 3 years and inability to complete the checklist. For all patients, a check list was completed that included: Age, family history of the disease, readmission, follow-up period, presence of soiling, complete or partial fecal incontinence, constipation, use of laxative, use of boogie, presence or absence of RectoAnal Inhibitory Reflex (RAIR) in manometers, stricture in rectal examination and enterocolitis before and after surgery. Data analysis was performed using SPSS software version 19. Results: Our patients were 4.81% male and 3.9% of them had an underlying disease, such as heart or kidney disease. Only 6.81% of them had to be re-admitted due to enterocolitis. Soiling was found in 5.39% of patients, complete and partial fecal incontinence were noted in 3.2% and 7.4% of them respectively. The incidence of fecal incontinency was 7%. Constipation occurred in 6.11% of cases and 3.9% of cases did not have RAIR in manometry. The incidence of rectal stenosis was 7% and 93% of patients had transitional zone (TZ) in barium enema before the operation. The result showed that there was no significant relationship between post- operative complications in both sexes (p<0.05). Conclusion: This study shows that the complications of Endorectal Transanal pull-through surgery as a method for treatment of Hirschsprung disease are infrequent. Therefore, this method can be considered as a selective method. Further investigations are recommended to prove this matter